2002
DOI: 10.1046/j.1532-5415.2002.50466.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Beliefs About Influenza, Pneumococcal Disease, and Immunizations Among Older People

Abstract: Educational campaigns to increase vaccination rates among older adults should focus on symptoms of, risk for, and severity of influenza and pneumococcal diseases and encouraging physicians to recommend the vaccines to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 11 publications
10
59
0
1
Order By: Relevance
“…12 Majority of the participants believed that healthy persons do not need the vaccine, 12 which was also in accordance to another study which was performed by Santibanez TA et al 14 Concerns regarding the cost of vaccine do not seem to be a major hindrance toward people getting vaccinated as similar finding was reported by Johnson DR et al in their study. 12 The study was conducted on low SES and High SES class patients visiting Civil Hospital and Aga Khan Hospital Karachi respectively.…”
Section: Discussionsupporting
confidence: 79%
“…12 Majority of the participants believed that healthy persons do not need the vaccine, 12 which was also in accordance to another study which was performed by Santibanez TA et al 14 Concerns regarding the cost of vaccine do not seem to be a major hindrance toward people getting vaccinated as similar finding was reported by Johnson DR et al in their study. 12 The study was conducted on low SES and High SES class patients visiting Civil Hospital and Aga Khan Hospital Karachi respectively.…”
Section: Discussionsupporting
confidence: 79%
“…An important share expressed fear of adverse events and lack of belief in the vaccine's efficacy or necessity. Another Brazilian study found these same reasons for non-compliance 23 , and similar motives were reported by elderly subjects in developed countries like the United Kingdom 17,24 , United States 25,26 , and Switzerland 27 .…”
Section: Reason N %supporting
confidence: 63%
“…36 All the participants counted a number of possible alternative ways that could prevent influenza, such as to stay at home, to avoid getting wet or chilled and to eat enough. 27 , 29 In our study all the individuals assumed that flu vaccine is the most effective preventive measure. In another research 27 the percentage was 65%.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several researchers suggested a number of reasons for low immunization rates or for refusal of influenza vaccination in the elderly population. 16 27 . Some other researchers have used theoretical models such as the Health Belief Model and the Multidimensional Locus of Control Theory to explain the low proportion of elderly vaccination.…”
Section: Introductionmentioning
confidence: 99%